2020
DOI: 10.1200/jco.2020.38.29_suppl.6
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning care coordination from the patient’s perspective.

Abstract: 6 Background: Cancer patients are frequently admitted to the hospital requiring medical oncologists to take an active role in coordinating with multiple teams. In an effort to redesign care to put patients at the center and address increasing demands on our medical oncologist’s time, we created the Oncology Coordinator (OC) role focused on care setting transitions. We aimed to evaluate whether the OC would improve quality of care and decrease healthcare utilization. Methods: The OCs, are non-clinical and serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, a prospective study conducted by Liu M.C, et al investigated the ability of target methylation analyses of cfDNA of different cancer types to detected and localize different cancer types. The authors concluded that cfDNA sequencing and analysis of methylation patterns detected more than 50 cancer types across different stages, including breast cancer [51].…”
Section: Early Diagnosis and Relapsementioning
confidence: 99%
“…Recently, a prospective study conducted by Liu M.C, et al investigated the ability of target methylation analyses of cfDNA of different cancer types to detected and localize different cancer types. The authors concluded that cfDNA sequencing and analysis of methylation patterns detected more than 50 cancer types across different stages, including breast cancer [51].…”
Section: Early Diagnosis and Relapsementioning
confidence: 99%